A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Streamlined Assessments are Integral to Operationalizing Resilience - Garrett Watson; Michael Deegan; Luke Hogewood; Andrew Jin; Holden Keebaugh; Frank Randon; Igor Linkov (Environmental Management, 2025)
As infrastructure systems face growing challenges from threats and increasing complexity, resilience has become a critical focus in sustaining essential services and managing risks. However, existing frameworks for assessing resilience are often impractical for owner-operators of critical infrastructure like dams and watersheds due to their complexity, extensive data requirements, and high costs. The failure of the Oroville Dam spillway in 2017, which resulted in mass evacuations and extensive damages, underscores the urgency for practical assessment strategies. This perspectives piece highlights the development of a streamlined resilience assessment approach co-developed with the U.S. Army Corps of Engineers’ Savannah District. Unlike traditional assessments that often become “one-and-done” exercises, our framework leverages simplified metrics, expert elicitation, and existing data to create adaptable and reproducible measures. By using a modified Analytical Hierarchy Process (AHP) to align resilience metrics with stakeholder priorities, this approach balances the need for comprehensive data with operational feasibility. Key insights suggest that streamlined assessments are integral to bridging the gap between resilience theory and practice, making it easier for decision-makers to evaluate and improve baselines consistently. Future efforts should emphasize metrics that are interpretable, prioritizable, and replicable to foster a culture of continuous improvement in resilience planning.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Filtration Behaviour of Ostrea edulis: Diurnal Rhythmicity Influenced by Light Cycles, Body Size and Water Temperature - Monica Fabra; Zoe Morrall; Luke Helmer; Gordon Watson; Joanne Preston (Estuaries and Coasts, 2025)
Despite the existing studies on oyster physiology, it is a concern that, by ignoring the diurnal rhythmicity of feeding activities, the current knowledge on oyster filtration might be unrepresentative of their real filtration capacity. In the present study, the diurnal and nocturnal fluctuations of Ostrea edulis clearance rate were investigated for the first time under laboratory conditions, also considering the combined effects of water temperature and oyster size. A positive correlation was found between the mean clearance rate (CR m ) and body size for both length and wet weight, with an average of 0.5 L h −1 and 0.1 L h −1 of water filtered by large and small adult oysters respectively during the 24-h experiment. A positive significant correlation between mean clearance rate and water temperature was found only for large oysters, suggesting further studies utilising temperature ranges closer to O. edulis thermal optimum are required to clarify the influence of temperature on oyster filtration activities across different size classes. The results of this study also showed a discontinuous ingestion of food by O. edulis throughout 24-h intervals, with higher values of clearance rate observed during hours of darkness at most temperatures for both size classes. This suggests photoperiod may have a potential influence on O. edulis filtration. Providing a better understanding of O. edulis filtration behaviour, these findings have implications for ecological restoration, aquaculture, and comparative studies on oyster bioenergetics and physiology, with direct applications to the development of predictive models and the assessment of ecosystem services provided by O. edulis habitat.

3D printed models are an accurate, cost-effective, and reproducible tool for quantifying terrestrial thermal environments - Karla Alujević; Leah Bakewell; Ian T. Clifton; Christian L. Cox; Luke O. Frishkoff; Eric J. Gangloff; Guillermo Garcia-Costoya; Matthew E. Gifford; Madison Glenwinkel; Samir A.K. Gulati; Alyssa Head; Monica Miles; et al. (Journal of Thermal Biology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Towards improved conversion of wet waste to jet fuel with atomic layer deposition-coated hydrodeoxygenation catalysts - W. Wilson McNeary; Jacob H. Miller; Sean A. Tacey; Jonathan Travis; Gabriella D. Lahti; Michael B. Griffin; Katherine L. Jungjohann; Glenn Teeter; Tugce Eralp Erden; Carrie A. Farberow; Luke Tuxworth; Michael J. Watson; et al. (Chemical Engineering Journal, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison of Single and Repeated Dosing of Anti-Inflammatory Human Umbilical Cord Mesenchymal Stromal Cells in a Mouse Model of Polymicrobial Sepsis - Barbara Fazekas; Senthilkumar Alagesan; Luke Watson; Olivia Ng; Callum M. Conroy; Cristina Català; Maria Velascode Andres; Neema Negi; Jared Q. Gerlach; Sean O. Hynes; Francisco Lozano; Stephen J. Elliman; et al. (Stem Cell Reviews and Reports, 2022)
Summary Mesenchymal stromal cells (MSCs) ameliorate pre-clinical sepsis and sepsis-associated acute kidney injury (SA-AKI) but clinical trials of single-dose MSCs have not indicated robust efficacy. This study investigated immunomodulatory effects of a novel MSC product (CD362-selected human umbilical cord-derived MSCs [hUC-MSCs]) in mouse endotoxemia and polymicrobial sepsis models. Initially, mice received intra-peritoneal (i.p.) lipopolysaccharide (LPS) followed by single i.p. doses of hUC-MSCs or vehicle. Next, mice underwent cecal ligation and puncture (CLP) followed by intravenous (i.v.) doses of hUC-MSCs at 4 h or 4 and 28 h. Analyses included serum/plasma assays of biochemical indices, inflammatory mediators and the AKI biomarker NGAL; multi-color flow cytometry of peritoneal macrophages (LPS) and intra-renal immune cell subpopulations (CLP) and histology/immunohistochemistry of kidney (CLP). At 72 h post-LPS injections, hUC-MSCs reduced serum inflammatory mediators and peritoneal macrophage M1/M2 ratio. Repeated, but not single, hUC-MSC doses administered at 48 h post-CLP resulted in lower serum concentrations of inflammatory mediators, lower plasma NGAL and reversal of sepsis-associated depletion of intra-renal T cell and myeloid cell subpopulations. Hierarchical clustering analysis of all 48-h serum/plasma analytes demonstrated partial co-clustering of repeated-dose hUC-MSC CLP animals with a Sham group but did not reveal a distinct signature of response to therapy. It was concluded that repeated doses of CD362-selected hUC-MSCs are required to modulate systemic and local immune/inflammatory events in polymicrobial sepsis and SA-AKI. Inter-individual variability and lack of effect of single dose MSC administration in the CLP model are consistent with observations to date from early-phase clinical trials. Graphical Abstract

Assessment of Gene Expression Biomarkers in the Chilean Pencil Catfish, Trichomycterus areolatus, from the Choapa River Basin, Coquimbo Chile - Jonathan M. Ali; Angela Montecinos; Thomas T. Schulze; Luke G. Allmon; Alex T. Kallenbach; Gabrielle F. Watson; Paul H. Davis; Daniel D. Snow; Angéline Bertin; Nicolas Gouin; Alan S. Kolok (Archives of Environmental Contamination and Toxicology, 2020)

Uncertainty in two-channel infrared remote sensing retrievals of a well-characterised volcanic ash cloud - Luke M. Western; Matthew I. Watson; Peter N. Francis (Bulletin of Volcanology, 2015)

Predicting the century‐long post‐fire responses of reptiles - Dale. G. Nimmo; Luke T. Kelly; Lisa M. Spence‐Bailey; Simon J. Watson; Angie Haslem; John G. White; Mike F. Clarke; Andrew F. Bennett (Global Ecology and Biogeography, 2012)
Aim We examined the century‐long post‐fire responses of reptiles to (1) determine the time‐scales over which fauna – fire relationships occur, (2) assess the capacity of a conceptual model to predict faunal response to fire, and (3) investigate the degree to which models of fauna – fire relationships can predict species occurrence and are transferable across space. Location A 104,000 km 2 area in the semi‐arid Murray Mallee region of south‐eastern Australia. Methods We surveyed reptiles at 280 sites across a century‐long post‐fire chronosequence. We developed generalized additive mixed models (GAMMs) of the relationship between time since fire and the occurrence of 17 species in two subregions, and compared modelled responses with predictions derived from the conceptual model. The predictive capacity of GAMMs was then assessed (1) within the subregion the model was developed and (2) when transferred into a novel subregion. Results Eleven species displayed a significant relationship with time‐since‐fire, with changes in species probability of occurrence continuing up to 100 years post‐fire. Predictions of the timing of species post‐fire peak in occurrence were accurate for 9 of 13 species models for which a significant fire response was detected, but little success was achieved in predicting the shape of a species' response. GAMMs predicted species occurrence more accurately when applied within the subregion in which they were developed than when transferred into a novel subregion, primarily due to some species responding to fire more strongly in one part of their geographic range. Main conclusions Fire influences the occurrence of reptiles in semi‐arid ecosystems over century‐long time frames. Habitat‐use conceptual models have value in predicting the peak occurrence of species following fire, particularly for species with distributions strongly shaped by fire. Species relationships with fire can differ across their geographic range, probably associated with variation in climatic influences on post‐fire succession and the consequent provision of habitat resources.